Sporadic acute hepatitis E in the United Kingdom: an underdiagnosed phenomenon?. Issue 5 (1st May 2000) - McCrudden, R; O'Connell, S; Farrant, T; Beaton, S; Iredale, J P; Fine, D
Abstract : BACKGROUND: Hepatitis E (HEV) is the primary cause of enterically transmitted non-A non-B hepatitis worldwide. Case reports of HEV in individuals in the United Kingdom relate to travel to endemic areas or contact with individuals who have visited these areas. CASE REPORTS: Four individuals presented with acute hepatitis to a hepatology clinic in a teaching hospital. Serology confirmed acute hepatitis E in all four. Investigation by the Communicable Disease Control Department established no links between the cases, no travel to an endemic area, and no contacts. CONCLUSION: Contrary to current belief, community acquired hepatitis E virus infection occurs sporadically in the United Kingdom and should be considered as a cause of seronegative hepatitis.